Acceptability of People Living with HIV who have Oral Problems for Reduced Sugar, High Protein Soybean Milk Candy - Singhato, Alongkote; Methajittipunt, Pornpen; Booranasuksakul, Uraiporn; Rueangsri, Narisa; Sobhon, Prasert (Journal of Nutrition Association of Thailand (Online), 2018)
Oral problems are one of the most deleterious health conditions commonly found in people living with HIV (PLHIV) which seriously affect the food intake and dietary habit. PLHIV with oral problems are at risk in loosing appetite and reduced food intake that can lead to malnutrition and muscle wasting. In addition, they are also facing hyperglycemia due to the antiretroviral drug’s side effects. This study, therefore, aimed to develop an acceptable high protein snack using the artificial sweeteners which is easy to chew and swallow for PLHIV with oral problems. From our previous survey soybean milk candy was the snack most favored by PLHIV; thus it was mixed with either refined sugar, or artificial sweeteners comprising of stevioside or sucralose at the same sweetening level, and isolated whey protein as the main source of dietary protein. To determine the participants’ satisfaction, thirty PLHIV with oral problems, who attend the Outpatient Department, Queen SavangVadhana Memorial hospital, were recruited to participate in this study to conduct the sensory evaluation. In general, results revealed significantly higher satisfaction scores on appearance, taste, and overall satisfaction (p<0.05) among participating PLHIV for formulae using sugar and sucralose than the formula using stevioside. In conclusion, the high protein soy bean milk candy using sugar and or sucralose were equally satisfying and well accepted by PLHIV with oral problems.